Phenomenological Psychology - Husserl, Edmund. author. aut Link
XIII, 179 p.
Keywords: THE TEXT In the summer semester of 1925 in Freiburg, Edmund Husserl delivered a lecture course on phenomenological psychology, in 1926127 a course on the possibility of an intentional psychology, and in 1928 a course entitled "Intentional Psychology. " In preparing the critical edition of Phiinomeno logische Psychologie (Husserliana IX), I Walter Biemel presented the entire 1925 course as the main text and included as supplements significant excerpts from the two subsequent courses along with pertinent selections from various research manuscripts of Husserl. He also included as larger supplementary texts the final version and two of the three earlier drafts of Husserl's Encyclopedia Britannica article, "Phenomenology"2 (with critical comments and a proposed formulation of the Introduction and Part I of the second draft by Martin Heidegger3), and the text of Husserl's Amsterdam lecture, "Phenomenological Psychology," which was a further revision of the Britannica article. Only the main text of the 1925 lecture course (Husserliana IX, 1-234) is translated here. In preparing the German text for publication, Walter Biemel took as his basis Husserl's original lecture notes (handwritten in shorthand and I Hague: Nijhoff, 1962, 1968. The second impression, 1968, corrects a number of printing mistakes which occur in the 1962 impression. 2 English translation by Richard E. Palmer in Journal o{ the British Society {or Phenomenology, II (1971), 77-90. 3 Heidegger's part of the second draft is available in English as Martin Heidegger, "The Idea of Phenomenology," tr. John N. Deely and Joseph A.